Women’s empowerment in action: Evidence from a randomized control trial in Africa - Bandiera, Oriana; Buehren, Niklas; Burgess, Robin; Goldstein, Markus; Gulesci, Selim; Rasul, Imran; Sulaiman, Munshi (World Bank, 2022)
Women in developing countries are disempowered relative to their contemporaries in developed countries. High youth unemployment and early marriage and childbearing interact to limit human capital investment and enforce dependence on men. In this paper, we evaluate an attempt to jump-start adolescent women’s empowerment in the world’s second-youngest country: Uganda. In this two-pronged intervention, adolescent girls are simultaneously provided vocational training and information on sex, reproduction and marriage. Relative to adolescents in control communities, after two years the intervention raises the likelihood that girls engage in income-generating activities by 72 per cent (mainly driven by increased participation in self-employment), and raises their monthly consumption expenditures by 41 per cent. Teen pregnancy falls by 26 per cent, and early entry into marriage/cohabitation falls by 58 per cent. Strikingly, the share of girls reporting sex against their will drops from 14 per cent to almost half that level and preferred ages of marriage and childbearing both move forward. The findings indicate that women’s economic and social empowerment can be jump-started through the combined provision of vocational and life skills, and is not necessarily held back by insurmountable constraints arising from binding social norms.